2011
DOI: 10.1103/physreva.83.013412
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot carrier-envelope-phase-tagged ion-momentum imaging of nonsequential double ionization of argon in intense 4-fs laser fields

Abstract: Single-shot carrier-envelope-phase (CEP) tagging is combined with a reaction mircoscope (REMI) to investigate CEP-dependent processes in atoms. Excellent experimental stability and data acquisition longevity are achieved. Using this approach, we study the CEP effects for nonsequential double ionization of argon in 4-fs laser fields at 750 nm and an intensity of 1.6 × 10 14 W/cm 2 . The Ar 2+ ionization yield shows a pronounced CEP dependence which compares well with recent theoretical predictions employing qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 30 publications
4
86
0
1
Order By: Relevance
“…In our present experimental studies on the CEP control of the deprotonation of acetylene, we employ CEP-tagged reaction microscopy (REMI) 24 (for details see the Methods section). The interaction of acetylene molecules with intense few-cycle pulses results in the dissociative ionization and isomerization of the molecule yielding a variety of reaction products 7 .…”
Section: Resultsmentioning
confidence: 99%
“…In our present experimental studies on the CEP control of the deprotonation of acetylene, we employ CEP-tagged reaction microscopy (REMI) 24 (for details see the Methods section). The interaction of acetylene molecules with intense few-cycle pulses results in the dissociative ionization and isomerization of the molecule yielding a variety of reaction products 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Taking advantage of recent progress in phase-tagging [32] to overcome these difficulties, we report in this Letter the measurement of CEP-dependent spatial asymmetries in the dissociation of H + 2 , from an ion beam, which we quantitatively compare with ab initio theory. Roudnev and Esry have shown that these CEP effects are due to interference of different photon number pathways to 1sσ g and 2pσ u final states, having opposite nuclear parity, whose relative phase is controlled by the CEP [33].…”
Section: Pacs Numbers: XXXmentioning
confidence: 99%
“…Even more insight into the process was gained in kinematically complete studies where the correlated two-electron momentum distributions were measured 11 and investigated for different laser parameters [12][13][14][15] . Measurements of the dynamics of NSDI in near-single cycle laser pulses have been restricted to recoil-ion spectra, which did not allow for the direct retrieval of the correlated electron-emission dynamics 16,17 . The sub-cycle dependence of electron correlation spectra has been explored by various theoretical studies, where the double-ionization dynamics were confined to a single cycle of a laser pulse 12,18 .…”
mentioning
confidence: 99%